You’re brought in as a workhorse and there's no real security here! Postdocs, precarity and the neoliberal university in South Africa - Hlatshwayo, Mlamuli Nkosingphile (PINS-Psychology in Society, 2024)
The literature on postdoctoral research fellows (hereafter postdocs) is bleak. Largely dominated by the global North scholars in the United Kingdom, the United States and Australia, this literature has provided an important insight into understanding the complex and nuanced experiences of postdocs and the struggles they encounter in navigating the publish or perish imperatives, the absence of a coherent pathway between the postdoc and permanent employment in academia and the constant job hopping that characterises the postdoc journey. In this paper, I share a portion of the findings of a national project focusing on three universities in South Africa, drawing on the experiences of current and former postdocs on the precarity, casualisation and job insecurity that they are facing. This is done through interviews with 23 current and former postdocs, a current university director of research and a former national department of higher education and training senior official. The findings reveal mainly two important aspects of the postdoc journey, 1) the crippling challenges of the employment insecurity and job insecurity on postdocs’ wellbeing and livelihood, as well as the 2) the often hidden, un-seen and invisible “motherhood penalty” that women postdoc experience in attempting to balance motherhood and the demands of the postdoc. I end the paper with concluding thoughts on the future of the postdoc system in higher education, and the urgent interventions that are required to support these marginalised and precarious scholars.